HAK WIRAUSAHA PEREMPUAN PERSPEKTIF MAQASID SYARIAH - Ahmad Mukri Aji; Harisah Harisah; Syarifah Gustiawati Mukri (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2020)
In today's modern era, it is not uncommon for women to be able to earn income by doing entrepreneurship, both traditional and modern with various perspectives. Entrepreneurial women are sometimes used to channel their hobbies, as well as being the backbone of the family to meet the needs of family life. So that the current rights of women entrepreneurs can be studied with the maqasid sharia approach. From this, researchers are interested in examining the rights of women entrepreneurs with a Sharia perspective. This study was conducted using a qualitative approach with literature data that was analyzed inductively and deductively. This study found that according to maqasid sharia women have rights in entrepreneurship, including the right to channel hobbies, which in the concept of maqasid sharia are included in the category of hifdzul aqli, the second right to earn income in the maqasid sharia concept is called hifdzul nafs.